PELATIHAN BUDIDAYA AYAM BROILER PADA KELOMPOK TERNAK MANDIRI DI KELURAHAN FITU TERNATE SELATAN - Emy Saelan,; Sri Utami,; Muhammad Ade Salim,; Yunus Syafie, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Training on broiler cultivation in Independent Livestock Groups is carried out with the aim that livestock groups understand broiler cultivation techniques, namely breeding, feeding and management, so as to produce optimal production and increase the economic income of livestock groups.The main problem that is often faced by broiler breeders, especially in the city of Ternate, is the high price of feed and limited availability, so many farmers are out of business.Through this activity, training is carried out on how to make broiler feed from locally available feed ingredients, easy to obtain, does not compete with human needs and the price is affordable for breeders, so as to produce quality rations and meet the standard of nutrient requirements for broiler growth. Formulation and techniques for making feed through training are carried out in a way that is simple and easy for farmers to understand. Feed making training through fermentation technology on the materials to be used, namely bran and EM4 for animal husbandry